Perspective matters: The internal/external frame of reference model for self- and peer ratings of achievement. (December 2017) - Lösch, Thomas; Kelava, Augustin; Nagengast, Benjamin; Trautwein, Ulrich; Lüdtke, Oliver
Abstract: The internal/external frame of reference (I/E) model posits that students' academic self-concept in one domain (e.g., math) is positively associated with achievement in the same domain but negatively associated with achievement in a comparison domain (e.g., English). Whereas academic self-concept encompasses self-ratings of achievement, peer academic reputation (PAR) encompasses peer ratings of the same achievement and PAR was shown to have an incremental predictive effect on a range of positive academic outcomes. Considering the importance of PAR, we hypothesized that the I/E model would also apply to PAR both as predictor and as outcome. We tested this hypothesis in a sample of 850 seventh-grade students in 47 classes in math and English. Therein, PAR was measured in a round-robin design where students rated each classmate's level of achievement. We tested I/E models with academic self-concept and PAR as outcomes. Results supported the I/E model for academic self-concept as outcome with academic achievement and PAR as predictor but not for PAR as outcome with achievement as predictor. For PAR as outcome, the effects across domains were positive rather than negative. These results were consistent across replications over three years using the same sample. Thus, whereas academic self-concept was characterized by contrasts between domains, PAR was characterized by assimilation between domains. Highlights: We compared the I/E model for self-vs. peer-rated achievement in English and math. Peer-rated achievement was assessed by asking students to rate each classmate. The I/E model held for self- but not for peer-rated achievement. In peer ratings, positive (not negative) cross-domain effects emerged. Dimensional comparisons affected peer perception differently than self-perception.